2021
DOI: 10.3390/jcm10174025
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in Stress, Coping Styles, and Life Satisfaction between the First and Second Waves of the COVID-19 Pandemic: A Longitudinal Cross-Lagged Study in a Sample of University Students

Abstract: In this study, we aimed to explain the interplay mechanism between stress, life satisfaction, and coping styles among university students. A cohort study was performed during the first (wave 1; W1) and second (wave 2; W2) waves of the Coronavirus disease 2019 (COVID-19) pandemic. The total sample included 231 university students, of which 59.31% were women. The Satisfaction with Life Scale (SWLS), Perceived Stress Scale (PSS), and Coping Inventory for Stressful Situations (CISS) were included in one online sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 92 publications
(147 reference statements)
12
41
0
1
Order By: Relevance
“…Lardier Jr et al examined the effect of coping style on well-being among Hispanic undergraduates, and found that higher level of stress was associated with higher level of reactive and suppressive coping style, which led to more subsequent depressive symptoms [14]. In addition, according to the similar research performed by Rogowska and colleagues during the Covid-19 pandemic, partial mediation effect of coping style was also found on the relationship between stress and life satisfaction among university students [19]. Based on these findings and the stress coping theory, we propose the second hypothesis (H2): Coping plays a mediating role in the association between Covid-19 pandemic-related stress and depressive symptoms among international medical students.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lardier Jr et al examined the effect of coping style on well-being among Hispanic undergraduates, and found that higher level of stress was associated with higher level of reactive and suppressive coping style, which led to more subsequent depressive symptoms [14]. In addition, according to the similar research performed by Rogowska and colleagues during the Covid-19 pandemic, partial mediation effect of coping style was also found on the relationship between stress and life satisfaction among university students [19]. Based on these findings and the stress coping theory, we propose the second hypothesis (H2): Coping plays a mediating role in the association between Covid-19 pandemic-related stress and depressive symptoms among international medical students.…”
Section: Introductionmentioning
confidence: 94%
“…A total score of 10 or higher indicates the presence of depressive symptoms, and previous studies have shown that the sensitivity and specificity were 88% and 88% respectively for detecting major depression [30,31]. The total score can be further categorized as mild depressive symptoms (10-15), moderate depressive symptoms (16)(17)(18)(19)(20)(21) and severe depressive symptoms (22-27) [30]. PHQ-9…”
Section: Measurement Of Depressive Symptomsmentioning
confidence: 99%
“…For example, Ochnik et al [7] compared the mental health of university students in nine countries. They revealed that Turkish students reported the highest depression levels (perhaps due to economic burden and a high unemployment rate), while Rogowska et al [20] showed an increase in perceived stress between the first and second wave of the pandemic in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is identical to that of Tyssen et al, according to whom doctors with low ES responded excessively to the stressful conditions imposed by their profession with implications for daily activities [ 66 ]. During COVID-19, levels of stress were higher, associated with avoidance of the use of coping mechanisms [ 67 ], but people with high ES could overcome these issues by following doctors’ recommendations [ 68 ]. Moreover, low levels of anxiety facilitate adaptability in all existential roles [ 69 ].…”
Section: Discussionmentioning
confidence: 99%